Sistem Pendukung Keputusan Seleksi Peserta Lomba Karnaval Murid TK Di Kabupaten Pidie Menggunakan Metode Multi Objective Optimization On The Basic Of Ratio Analysis (MOORA) Berbasis Web - Putri, Adinda Nasa; Husaini; Setiawati, Cut Lilis (Yayasan Sagita Akademia Maju, 2024)
Kindergarten is an example of an educational sector that has been impacted by advances in computer technology. One of the most important parts of a kindergarten is student assessment and the creativity of school children. In one kindergarten there are dozens of students and each has different creativity values. However, there are problems at the Pidie Regency Education Office in assessing the process of determining the selection as the best participant to take part in the kindergarten student carnival competition in Pidie Regency. This writing will discuss the design of a decision support system using the Multi-Objective Optimization On The Basis Of Ratio Analysis (MOORA) method to select participants in the kindergarten student carnival competition in Pidie Regency. The aim of this research is to assist the Pidie District Education Office in making decisions by evaluating and ranking existing alternatives so that it is easier to determine which kindergarten student participants can take part in the carnival competition. The programming language used in designing this application is PHP using the CodeIgniter framework and HTML. For display using CSS3, namely using the Bootstrap and Jquery framework. The database uses MySQL. The tools and editors used are XAMPP for Windows, and Microsoft Visual Studio Code. The final result of this system is to provide a recommendation output ranking participants from the largest alternative value to the smallest. With this system, the Education Department will be helped and made easier in determining competition participants.